Ras/MAPK Modifier Loci Revealed by eQTL in Caenorhabditis elegans. Issue 9 (1st September 2017) - Sterken, Mark G; van Bemmelen van der Plaat, Linda; Riksen, Joost A G; Rodriguez, Miriam; Schmid, Tobias; Hajnal, Alex; Kammenga, Jan E; Snoek, Basten L
Abstract: The oncogenic Ras/MAPK pathway is evolutionarily conserved across metazoans. Yet, almost all our knowledge on this pathway comes from studies using single genetic backgrounds, whereas mutational effects can be highly background dependent. Therefore, we lack insight in the interplay between genetic backgrounds and the Ras/MAPK-signaling pathway. Here, we used a Caenorhabditis elegans RIL population containing a gain-of-function mutation in the Ras/MAPK-pathway gene let-60 and measured how gene expression regulation is affected by this mutation. We mapped eQTL and found that the majority (∼73%) of the 1516 detected cis -eQTL were not specific for the let-60 mutation, whereas most (∼76%) of the 898 detected trans -eQTL were associated with the let-60 mutation. We detected six eQTL trans -bands specific for the interaction between the genetic background and the mutation, one of which colocalized with the polymorphic Ras/MAPK modifier amx-2 . Comparison between transgenic lines expressing allelic variants of amx-2 showed the involvement of amx-2 in 79% of the trans -eQTL for genes mapping to this trans -band. Together, our results have revealed hidden loci affecting Ras/MAPK signaling using sensitized backgrounds in C. elegans . These loci harbor putative polymorphic modifier genes that would not have been detected using mutant screens in single genetic backgrounds.